2022
DOI: 10.3390/v14050868
|View full text |Cite
|
Sign up to set email alerts
|

Early and Longitudinal Humoral Response to the SARS-CoV-2 mRNA BNT162b2 Vaccine in Healthcare Workers: Significance of BMI, Adipose Tissue and Muscle Mass on Long-Lasting Post-Vaccinal Immunity

Abstract: Background: This study aimed to investigate the early and longitudinal humoral response in Healthcare Workers (HCWs) after two doses of the BNT162b2 vaccine and to assess the association between metabolic and anthropometric parameters and the humoral response after vaccination. Methods: The study included 243 fully vaccinated HCWs: 25.50% previously infected with SARS-CoV-2 (with prior history of COVID-19—PH) and 74.40%—uninfected, seronegative before the first vaccination (with no prior history of COVID-19—NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 72 publications
(78 reference statements)
4
12
1
Order By: Relevance
“…The booster again elucidated a humoral response, resulting in positive values of anti-SARS-CoV-2 IgG titers (≥10 AU/mL) in all study participants. However, the mean IgG antibody titer after the third dose was about 3-fold lower compared to the results obtained after administration of the second vaccine dose described in our previous study [ 16 ]. Contrary results were obtained by Skorupa et al, who reported significantly higher levels of anti-SARS-CoV-2 IgG antibodies after the BNT162b2 booster compared to those achieved after the second dose [ 31 ].…”
Section: Discussioncontrasting
confidence: 81%
See 4 more Smart Citations
“…The booster again elucidated a humoral response, resulting in positive values of anti-SARS-CoV-2 IgG titers (≥10 AU/mL) in all study participants. However, the mean IgG antibody titer after the third dose was about 3-fold lower compared to the results obtained after administration of the second vaccine dose described in our previous study [ 16 ]. Contrary results were obtained by Skorupa et al, who reported significantly higher levels of anti-SARS-CoV-2 IgG antibodies after the BNT162b2 booster compared to those achieved after the second dose [ 31 ].…”
Section: Discussioncontrasting
confidence: 81%
“…We investigated the IgG antibody-mediated response to three doses of the BNT162b2 vaccine, focusing particularly on a booster-induced response. Interestingly, the most significant increase in anti-SARS-CoV-2 IgG antibody titers on the timeline was observed after administration of the second vaccine dose (early follow-up), as described previously [ 16 ]. At that measurement point, only two participants had non-reactive values of anti-SARS-CoV-2 IgG titers.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations